A preliminary study on promoting e-book about halal industry framework in Malaysia for public awareness in Malaysia - Awang, Asmaa; Hazahari, Noor Yuslida; Al-Saari, Nurhidayu (Atlantis Press, 2023)
Malaysia’s halal industry is one of the most well-known in the world. However, some Malaysians still believe that halal scopes in Malaysia only apply to the food and beverage industries. Hence, the main objective of this study is to assess public awareness and knowledge of the halal industry framework in Malaysia. This study uses a quantitative approach with 154 respondents from all over Malaysia. Findings show that most people are aware of the halal industry framework, but only those who have experience in the halal industry have the knowledge about halal industry framework and how to contact the appropriate authority to deal with it. In conclusion, this result adds to the evidence of the importance of this project to educate Malaysians about the halal industry framework in Malaysia.